Markov chain model and stationary test: a case study on Malaysia Social Security (SOCSO) - Shamshimah Samsuddin,; Noriszura Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Recently, the Markov chain model, which is a model that depends on the probability of transition, has been widely used in areas related to health problems. This article aims to build the yearly transition model for the health state of workers who contribute under the Employment Injury Scheme (EIS) SOCSO in Malaysia using the Markov chain model. In addition, the stationary test is carried out to confirm whether the model can be used for the projection of transition probabilities of the contributors’ health levels.